FORMATION OF VIEWS AND INTERESTS TO THE ACCOUNTANTS PROFESSION IN MASTER OF ACCOUNTING STUDENTS OF JEMBER UNIVERSITY FORCE OF 2016 USING STRUCTURATION THEORY ANALYSIS - Munadzir Ahsan Al Ghofiqi (UPT Penerbitan Universitas Jember)
This study regarding the establishment of the views and interests to the accountant profession in the students of Master of Accounting Jember University Force of 2016 using structuration theory analysis. Structuration theory is more focused on what the actor rather than what he says. This study uses ethnometodology perspective. The method used the qualitative. Selection of informants by several criteria that only some active students in college, working as practitioners and academics. The discussion this time relate to the views of students to the accounting profession. They get the information early to think about the accounting profession, which is negotiating with the structure. In the context of actors and social structures indicate the starting point of the relationship in the consciousness of the subjects that are internal. Giddens differentiate into three internal dimensions are unconscious motivation, practical consciousness and discursive consciousness. Then have the student will view his interest in the post-graduate profession. The accounting profession is a profession that is not directly understood by the agent, because at the time of choosing the road to continue his studies led to the thought process. The existence of space and time is what the overall role of the social part is. Researchers find a wide variation in students during the negotiation process with the structure that is the type of students their own accord, neutral and demand/coercion.